Oxidation of a Dipeptide by N-Bromophthalimide in Aqueous Acetic Acid Medium and Comparison with Monomer Glycine: A Kinetic and Mechanistic Study - Anjum, Amena; Srinivas, P. (Asian Journal of Chemistry, 2010)
The oxidation reactions of dipeptide, glycylglycine have been carried out with N-bromophthalimide in presence of mercuric acetate. The kinetics revealed first order dependence on N-bromophthalimide and fractional order dependence on glycylglycine. Michaelis-Menten type mechanism was proposed. Thermodynamic parameters have been evaluated. The oxidation reactions were compared to that of the monomer glycine.